2023
DOI: 10.1158/1055-9965.epi-22-0738
|View full text |Cite
|
Sign up to set email alerts
|

Area-level Socioeconomic Disadvantage and Cancer Survival in Metropolitan Detroit

Abstract: Background: Racial segregation is linked to poorer neighborhood quality and adverse health conditions among minorities, including worse cancer outcomes. We evaluated relationships between race, neighborhood social disadvantage, and cancer survival. Methods: We calculated overall and cancer-specific survival for 11,367 non-Hispanic Black (NHB) and 29,481 non-Hispanic White (NHW) individuals with breast, colorectal, lung, or pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 66 publications
2
2
0
Order By: Relevance
“…However, we were unable to compare results with individual‐level education due to unavailable information in the SEER program. Another study, using the area deprivation index (ADI) (education is one of the indicators), found that increasing ADI was associated with a 1.1‐fold increased risk of CRC mortality in Black patients 17 . Therefore, these previous studies demonstrate that racial minorities and lower SES are more likely to experience poorer survival outcomes, which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, we were unable to compare results with individual‐level education due to unavailable information in the SEER program. Another study, using the area deprivation index (ADI) (education is one of the indicators), found that increasing ADI was associated with a 1.1‐fold increased risk of CRC mortality in Black patients 17 . Therefore, these previous studies demonstrate that racial minorities and lower SES are more likely to experience poorer survival outcomes, which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…area deprivation index (ADI) (education is one of the indicators), found that increasing ADI was associated with a 1.1-fold increased risk of CRC mortality in Black patients. 17 Therefore, these previous studies demonstrate that racial minorities and lower SES are more likely to experience poorer survival outcomes, which is consistent with our findings. SES and racial disparities can in part explain CRC patient inequalities in access to early detection, suitable and appropriate quality care, and survival.…”
Section: Model 1 Csupporting
confidence: 92%
See 2 more Smart Citations
“…In another study, 15 neighborhood deprivation was associated with increased breast cancer mortality among White women, but a nonsignificant decrease was found among Black women. Nevertheless, other studies have reported no effect measure modification by race, with neighborhood deprivation increasing breast cancer mortality among both Black and White women, [11][12][13] or having no impact in either group. 16 The present study is, to our knowledge, the first attempt to uncover potential race-specific heterogeneity in the association between neighborhood deprivation and breast cancer mortality by investigating multiple stratifying factors representing access to health care, social cohesion, and residential racial segregation.…”
Section: Discussionmentioning
confidence: 90%